Optimalisasi Limbah Sekam Padi sebagai Produk Arang Sekam Padi untuk Meningkatkan Nilai Jual di Desa Legundi, Kabupaten Karangjati - Rantau Naufal Abroor; Dinta Artriana Wiguna; Muhammad Afwan Saputro; Florentina Anggita Tiara Larasati; Anastasia Putri Agung Febriana; Maritza Octariani Putri; Aurelia Nadira Rosekania Darmawan; Karisa Arfina Ratri; Firda Rizki Nafiza Ahmad; Dewi Sundari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The abundant rice husk waste in Legundi Village, Ngawi Regency, has not been used optimally and has the potential to cause environmental pollution. On the other hand, rural communities, especially the PKK Women's group, need business diversification to increase family income. Responding to these challenges, this community service program is carried out with the main objectives: (1) utilizing rice husk waste into husk charcoal products with economic value as a planting medium; (2) increasing income and empowering community groups; and (3) strengthening the capacity of digitizing MSMEs through online marketing assistance. The activity was carried out with a participatory method that prioritized the active involvement of the community. There are two main approaches to program implementation. First, training on the practice of making husk charcoal uses imperfect combustion techniques that are simple and environmentally friendly. Second, assistance in the digitalization of MSMEs which includes training in creating and managing e-commerce accounts (Shopee and Tokopedia), the production of visual and narrative-based promotional content, and digital marketing strategies that are adaptive to consumer trends. The results of the activity show that the community is able to process husk waste into packaged husk charcoal products with the brand